Association between trans fatty acids and COVID‐19: A multivariate Mendelian randomization study. Issue 2 (10th January 2023) - Liu, Xuxu; Du, Zhiwei; Wang, Jing; Wang, Qiang; Zheng, Yi; Niu, Le; Hao, Chenjun; Xue, Dongbo; Zhang, Yingmei
Abstract: Traditional observational studies have suggested a potential association between trans fatty acids (TFAs), which are considered to be health‐damaging fatty acids, and coronavirus disease 2019 (COVID‐19). However, whether there is a causal relationship between them is currently unclear. We aimed to investigate the causal link between genetically determined TFAs and COVID‐19. We performed univariate and multivariate Mendelian randomization (MR) studies using summary statistics from the European Pedigree TFAs ( n = 8013), COVID‐19 susceptibility ( n = 159 840), COVID‐19 hospitalization ( n = 44 986), and COVID‐19 severity ( n = 18 152) genome‐wide association studies (GWAS). The inverse variance weighted (IVW) method was used as the primary MR analysis, and several other methods were used as supplements. In univariate MR analysis, higher levels of circulating trans, cis‐18:2 TFAs were positively associated with a higher COVID‐19 hospitalization rate ( p < 0.0033; odds ratio [OR] = 1.637; 95% confidence interval [CI]: 1.116–2.401) and COVID‐19 severity ( p < 0.0033; OR = 2.575; 95% CI: 1.412–4.698). Furthermore, in multivariate MR analysis, trans, cis‐18:2 had an independent and significant causal association with a higher COVID‐19 hospitalization rate ( p = 0.00044; OR = 1.862; 95% CI = 1.316–2.636) and COVID‐19 severity ( p = 0.0016; OR = 2.268; 95% CI = 1.361–3.779) after the five TFAs were adjusted for each other. Together, our findings provide evidence that trans, cis‐18:2 TFAs have an independent and robust causal effect on COVID‐19 hospitalization and severity.